Pelatihan Perpajakan PPH 21 Orang Pribadi Untuk Mewujudkan Kesadaran Pajak Generasi Z di SMK Islam Manba’ul Ulum Mayong Jepara - P, Purwati; Wardani, Nila Ayu Kusuma; Ulum, Abdullah Ahnafil; Syarifudin, Muhammad; Febriyan, Rizky Maulana (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
The younger generation, including millennials, is an important component in national development. Generation Z can occupy important positions in the future. Therefore, the level of knowledge and awareness of taxes is strategic and important to understand. The lack of public tax awareness is caused by ignorance about taxation. Building tax awareness needs to be built from school. As one of these efforts, community service was carried out at SMK Islam Manba'ul Ulum Mayong Jepara. The obstacles faced were the lack of introduction and knowledge of calculating personal income tax and the difficulty in explaining material related to calculating Personal Income Tax to students. The form of the solution, based on a joint agreement with SMK Islam Manba'ul Ulum, was to provide training aimed at realizing Generation Z's tax awareness starting from students' knowledge and understanding of taxation, especially Personal Income Tax Article 21 in Indonesia, both in theory and practice, especially its benefits and applications in the world of education. The training was given to 75 students of class XI Office Management Automation using lecture and practice methods, through the stages of providing general tax introduction material, Income Tax material and practice questions based on real cases. The results obtained from this training are an increase in students' knowledge and understanding in working on PPh tax transaction case study questions, the percentage of participants with exam scores above KKM reaching 97%.